Identification of novel biomarkers of inflammation in Atlantic salmon (Salmo salar L.) by a plasma proteomic approach. (February 2022) - Sun, Baojian; van Dissel, Dino; Mo, Ingrid; Boysen, Preben; Haslene-Hox, Hanne; Lund, Hege
Abstract: Monitoring fish welfare has become a central issue for the fast-growing aquaculture industry, and finding proper biomarkers of stress, inflammation and infection is necessary for surveillance and documentation of fish health. In this study, a proteomic approach using mass spectrometry was applied to identify indicators of the acute response in Atlantic salmon blood plasma by comparing Aeromonas salmonicida subsp. salmonicida infected fish and non-infected controls. The antimicrobial proteins cathelicidin (CATH), L-plastin (Plastin-2, LCP1) and soluble toll-like receptor 5 (sTLR5) were uniquely or mainly identified in the plasma of infected fish. In addition, five immune-related proteins showed significantly increased expression in plasma of infected fish: haptoglobin, high affinity immunoglobulin Fc gamma receptor I (FcγR1, CD64), leucine-rich alpha 2 glycoprotein (LRG1), complement C4 (C4) and phospholipase A2 inhibitor 31 kDa subunit-like protein. However, various fibrinogen components, CD209 and CD44 antigen-like molecules decreased in infected fish. Selected biomarkers were further verified by Western blot analysis of plasma and real time PCR of spleen and liver, including CATH1, CATH2 and L-plastin. A significant increase of L-plastin occurred as early as 24 h after infection, and a CATH2 increase was observed from 72 h in plasma of infected fish. Real time PCR of selected genes confirmed increased transcription of CATH1 and CATH2. In addition, serum amyloid A mRNA significantly increased in liver and spleen after bacterial infection. However, transcription of L-plastin was not consistently induced in liver and spleen. The results of the present study reveal novel and promising biomarkers of the acute phase response and inflammation in Atlantic salmon. Highlights: Biomarkers of inflammation in salmon found by a plasma proteomic approach. Cathelicidins and L-plastin are indicators in blood for bacterial infection. Haptoglobin, FcγR1, LRG1 and C4 increase after A. salmonicida infection. Fibrinogen, CD209 and CD44 decrease after A. salmonicida infection.